Use of clopidogrel and proton pump inhibitors after a serious acute coronary event: Risk of coronary events and peptic ulcer bleeding - Rodríguez, Luis A. García; Johansson, Saga; Soriano, Lucía Cea (Thrombosis and Haemostasis, 2013)
Some pharmacokinetic studies have reported that proton pump inhibitors (PPIs) reduce the activity of clopidogrel, but the results of studies assessing clinical outcomes in patients receiving both drugs are inconsistent. We have therefore carried out a population-based cohort study with nested case–control analysis, in order to evaluate changes in the risk of cardiovascular and peptic ulcer bleeding (PUB) events associated with PPI use in patients receiving clopidogrel. A total of 42,542 patients aged 50–84 years in 2000–2007 who survived an acute coronary event were identified in two UK-based primary care databases (The Health Improvement Network and the General Practice Research Database). Individuals were followed up to identify incident cases of non-fatal myocardial infarction/coronary death (n = 2,546) and PUB (n = 194). Controls were frequency matched to cases by age, sex and calendar year. Compared with PPI non-use, current continuous PPI use was not associated with a significant change in risk of non-fatal myocardial infarction/coronary death among current continuous users of clopidogrel monotherapy (relative risk [RR], 1.06; 95% confidence interval [95% CI], 0.47 to 2.36) or dual antiplatelet therapy (DAT; RR, 0.80; 95% CI, 0.47 to 1.37) who initiated their antiplatelet therapy shortly after their coronary event. Among patients prescribed DAT at the start date, the RR of PUB events associated with current PPI use initiated at the start date was 0.66 (95% CI, 0.27 to 1.60).
Keywords: Clopidogrel; proton pump inhibitors; drug interactions